2017
DOI: 10.1080/13880209.2017.1296002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of chlorogenic acid in beagles after oral administrations of single compound, the extracts of Lonicera japanica , and the mixture of chlorogenic acid, baicalin, and Forsythia suspense

Abstract: Context: Chlorogenic acid (ChA) is the major compound in Shuang-Huang-Lian (SHL), which is mainly composed of ChA, baicalin, and Forsythia suspense Thunb Vahl.Objective: The effects of co-existing compounds in SHL and Lonicera japanica Thunb on the absorption of ChA was investigated.Materials and methods: According to 3 × 3 Latin-square test, ChA alone, the extracts of Lonicera japanica, or the mixture of ChA, baicalin and Forsythia suspense (ChA effective doses is 60 mg/kg) was separately given to six beagles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…In the present study, the pharmacokinetic parameters of the components in plasma revealed some differences compared with previous researches [16][17][18][19][20][21][22][23]. Danshensu, protocatechuic acid, isoquercitrin, and ferulic acid were quickly absorbed, and their peak concentrations occurred at 0.47 h, 0.50 h, 0.50 h, and 0.17 h, respectively, while stachydrine, baicalin, and baicalein were absorbed much slower than other components for the average T max values which were 3.20 h, 2.80 h, and 3.60 h, respectively.…”
contrasting
confidence: 87%
See 1 more Smart Citation
“…In the present study, the pharmacokinetic parameters of the components in plasma revealed some differences compared with previous researches [16][17][18][19][20][21][22][23]. Danshensu, protocatechuic acid, isoquercitrin, and ferulic acid were quickly absorbed, and their peak concentrations occurred at 0.47 h, 0.50 h, 0.50 h, and 0.17 h, respectively, while stachydrine, baicalin, and baicalein were absorbed much slower than other components for the average T max values which were 3.20 h, 2.80 h, and 3.60 h, respectively.…”
contrasting
confidence: 87%
“…Hedyotis diffusa, a traditional Chinese medicine belongs to the Rubiaceae family, has been widely used for the treatment of various inflammation-related diseases, including appendicitis, arthritis, rheumatism, and urethral infection in China. In addition, the activities of Leonurus, Radix Salviae miltiorrhizae, and Angelica primarily focus on improvement of nourishing blood, promoting blood circulation, and resolving dampness [9][10][11][12][13][14][15][16][17][18][19][20]. A previous study has shown that the combined application of Angelica and Radix Salviae miltiorrhizae could exert the function of activating blood and promoting the production of new blood [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, sows fed FSE tended to have a higher relative abundance of Lactobacillus at genus level in feces at weaning, the beneficial bacteria might pass from sows to their offspring, which was possibly a pathway of maternal FSE on modulating gut barrier function and health status in suckling piglets (67). This finding helped explain the improved immunity, anti-inflammatory functions, and ADG in piglets, since Lactobacillus, serving as a probiotic, could effectively increase the expression of IL-10 and TGF-β and decrease the expression of some pro-inflammatory cytokines (such as TNF-α and IL-6) in the colon (68), and thus decreased diarrhea and improved performance in suckling piglets (69). This finding might be due to that the forsythiaside in FSE could enhance the levels of Bifidobacteria, Lactobacillus, and other beneficial microbial community (10).…”
Section: Discussionmentioning
confidence: 89%
“…We used the same route of administration, but considering that LPS-induced ALI has an acute clinical course, we shortened the administration period to 7 days and adjusted the concentration so that the total dosage was approximately equivalent to that of previous studies. In another study on beagle dogs (Liu et al, 2017), CGA was determined in the blood with a C max of 2.350 ± 0.483 μgÁml À1 for a dose of 60 mgÁkg À1 over 7 days. This concentration was higher than that in the present study due to species differences of the experimental animals selected.…”
Section: Drug Concentrationsmentioning
confidence: 99%